Gaya Hidup Remaja Terhadap Belanja Online Shop Menggunakan Aplikasi Shopee Kota Pontianak - Mira Wulandari; Armuli Armuli; Septyanika Alamanda (Jurnal Syntax Admiration, 2024)
The influence of the internet on the community environment is very influential, because the internet can bring a very wide network for customers or teenagers to choose alternative shopping online. The support of an online application system can make it easier for teenagers to see applications just shopping online in the onlineshop application, so that the attraction to shop through online or e-commerce can be an attraction for teenagers to facilitate them in the process of selecting and purchasing the desired product. Basically, the shopee application is an online shopping platform that is in great demand because it is a platform that is tailored for the region and provides an easy and fast online shopping experience for teenagers through strong support and logistics. The purpose of this study is to find out how the lifestyle of teenagers in Pontianak City towards online shopping using the shopee application. The research method that will be used in this study is using quantitative methods, with this research will use survey methods. Research hypothesis: the research hypothesis used is descriptive analysis carried out through testing descriptive hypotheses. The result of the analysis is whether the research hypothesis can be generalized or not.